Are people willing to take regular vaccinations? A qualitative study among diverse ethnic groups in Hong Kong - Yan Li; Ivy Yan Zhao; Wenze Lu; Sau Fong Leung; Daniel Bressington; Lin Yang; Yao Jie Xie; Mengqi Li; Angela Y. M. Leung (PLoS ONE, 2025)
Vaccine hesitancy is identified as one of the top ten global health threats by the World Health Organization. The emergence of new coronavirus variants and evidence of waning immunity offered by COVID-19 vaccines draw attention to the need for regular vaccinations. This study aimed to understand the people’s hesitancy towards regular COVID-19 vaccination among diverse ethnic groups of citizens in Hong Kong. A qualitative descriptive research approach was adopted. Content analysis was used for data analysis. A purposive sample of fifteen participants, aged 20–75, with diverse ethnicities (Chinese, Palestinian, British, French and Indian) joined the study. Their barriers and hesitancy toward taking the COVID-19 vaccination included personal beliefs and biases, policies and ethical considerations, and concerns about vaccines and vaccination. Collaborative efforts of governments, health policymakers, healthcare providers, media sources and vaccine manufacturers are required to decrease vaccine hesitancy. Cultural values and ethical issues should be considered in vaccine promotion. This study contributes to the existing body of literature by exploring vaccine hesitancy among ethnically diverse populations during the COVID-19 pandemic. The findings provide critical insights into the underlying reasons driving vaccine hesitancy among ethnic groups in Hong Kong and support the development of targeted public health strategies to address this issue. Public health researchers and practitioners are encouraged to prioritize addressing mistrust and ethical concerns while leveraging the strengths of multicultural communities and fostering coordinated efforts among diverse organizations to reduce vaccine hesitancy against future global health challenges.